Putting Socrates back in Socratic method: Theory-based debriefing in the nursing classroom - Dinkins, Christine Sorrell (Nursing philosophy, 2019)
The term "Socratic method" is so pervasive in education across the disciplines that it has largely lost its meaning, and it has lost its roots in its originator—the historical Socrates. In this article we draw from the original source, Plato's ancient dialogues, to understand the theory and principles behind the questioning used in Socratic method. A deep understanding of Socratic method is particularly timely now as nursing leaders call for increased use of theory-based debriefing across the nursing curriculum. Socratic questioning is ideally suited as a method for debriefing in nursing classrooms because of its ability to enhance critical thinking and self-reflection of the learner and because of its basis in care for the learner through a learner-centred design. We present an analysis of the Socratic method in Plato's works and provide an overview of the key Socratic principles and techniques. We illustrate these principles and techniques with examples of how Socratic teaching can be applied in the nursing classroom, and we address the challenges and rewards for nursing faculty implementing Socratic method. Learning about Socratic method directly from Plato's dialogues can provide a richer and more robust understanding of this key pedagogical technique and help nurse educators practice more intentional and informed Socratic questioning and debriefing.